EFFECTS OF DANCE EDUCATİON ON EMOTİONAL İNTELLİGENCE RELATED OUTCOMES - Atamturk, Hakan; Dincdolek, Bilgen (Revista Gênero e Interdisciplinaridade, 2021)
Background and Study Aim: Dance can be interpreted as a language that the human body speaks. Through bodily movements when performing dance, individuals can express their emotions and communicate with others. Emotional intelligence entails an individual’s being aware of his own emotions, the ways he manages these emotions, self-motivation, realising other peoples’ emotions and the ability to establish relationships (Goleman, 1996). Even the definitions of dance and emotional intelligence suggest an association. Hence, this study aimed to explore the potential associations between dance education and emotional intelligence abilities. Material and Methods: The data were collected from a total of 100 adolescents who were enrolled in five dance schools in North Cyprus and from 100 adolescents who did not dance through the Emotional Intelligence Scale which was developed by Atamturk (2011). The Mann-Whitney U-Test results indicated a significant difference between the emotional intelligence abilities of adolescents who received dance education and those of adolescents who did not. Additionally, Kruskal- Wallis test indicated that dance expertise significantly influenced the emotional intelligence development of the participants. Results: Adolescents who received dance education developed higher levels of emotional intelligence abilities and dance expertise affected the emotional intelligence development of the adolescents. In this respect, this study adds a novel variable to be investigated to the relevant literature. Conclusions: As the results of this study indicates dance can help adolescents lead a healthier life by increasing emotional intelligence development. Further research can delve into the impact of the dance expertise on emotional intelligence.